PENGARUH STABILITY OF SALES, GROWTH OPPORTUNITY DAN CURRENT RATIO TERHADAP DEBT TO EQUITY RATIO PADA PERUSAHAAN SEKTOR PROPERTY AND REAL ESTATE YANG TERDAPAT DI BURSA EFEK INDONESIA PERIODE 2014-2017 - Yusneni Afrita Nasution (Fakultas Ekonomi Prodi Akuntansi, 2020)
The objective of the research was to examine and analyze the influence of stability of sales, growth opportunity and current ratio on debt to equity ratio in property and real estate sub-sector companies listed in the Indonesia Stock Exchange period 2014-2017. The research used descriptive research methode. The population was 49 companies in the property and real estate subsector listed in the Indonesia Stock Exchange for the period 2014 – 2017, and 31 of them were used as the samples, taken by using purposive sampling technique. The data were analyzed by using multiple linear regression using SPSS. The results of the research showed that the variables of Stability of Sales, Growth Opportunity and Current Ratio simultaneously had influence on Debt to Equity Ratio. Partially, Stability of Sales had negative and insignificant influence on Debt to Equity Ratio, Growth Opportunity had positive and insignificant influence on Debt to Equity Ratio and Current Ratio had negative and significant influence on Debt to Equity Ratio.